2017
DOI: 10.1108/rpj-04-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Current state and potential of additive – hybrid manufacturing for metal parts

Abstract: Purpose This paper aims to investigate the extent to which traditional manufacturers are equipped and interested in participating in a hybrid manufacturing system which integrates traditional processes such as machining and grinding with additive manufacturing (AM) processes. Design/methodology/approach A survey was conducted among traditional metal manufacturers to collect data and evaluate the ability of these manufacturers to provide hybrid – AM post-processing services in addition to their standard produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
0
17
0
7
Order By: Relevance
“…This section discusses the main challenges of the hybrid AM technology for producing metal parts. Strong et al [185] reported a survey among traditional manufacturers that highlighted the open issues associated with the access of metal AM systems, process engineering, tooling requirement (tool access) and part quality control. In addition, it was noted that hybrid processes combining AM with machining technologies are not yet applicable in many industrial sectors due to the size limitations of AM systems.…”
Section: Challenges Of Hybrid Additive Manufacturingmentioning
confidence: 99%
“…This section discusses the main challenges of the hybrid AM technology for producing metal parts. Strong et al [185] reported a survey among traditional manufacturers that highlighted the open issues associated with the access of metal AM systems, process engineering, tooling requirement (tool access) and part quality control. In addition, it was noted that hybrid processes combining AM with machining technologies are not yet applicable in many industrial sectors due to the size limitations of AM systems.…”
Section: Challenges Of Hybrid Additive Manufacturingmentioning
confidence: 99%
“…Soon, 4D printing will face challenges in computing, research, and engineering and is expected to reach a plateau of productivity in around ten years (Gartner 2018). Metal AM also offers unrivalled design freedom with the ability to manufacture parts from a wide range of materials (Salmi et al 2012;Strong et al 2017). The metal AM grew 41.9% in 2018 to an estimated $260.2 million, up from $183.4 million in 2017.…”
Section: Additive Manufacturing: Theoretical Underpinningsmentioning
confidence: 99%
“…Rapid prototyping has been referred to as a technology (Khajavi et al, 2014;Lindemann et al 2012), as a process (Achillas et al, 2014;Rogers et al, 2017;Strong et al, 2017) and as an application of AM-related technologies (Gress and Kalafsky, 2015;Jha, 2016;Feldmann and Pumpe, 2017). Similarly, the literature refers to rapid manufacturing as a technology (Lindemann et al 2012;Sasson and Johnson, 2016), as a process ( Huang et al, 2013;Oettmeier and Hofmann, 2016;Ryan et al, 2017), and as an application of AM-related technologies (Meisel et al,2016;Attaran, 2017;Ortt, 2017).…”
Section: Terminologies Used In the Am Technologies Literaturementioning
confidence: 99%
“…AM + SP ( Berman 2012;Durão et al 2017;Jha 2016;Pérès and Noyes, 2006;Pour and Zanoni 2017;Zanardini et al 2016) 6 AM + SC (Achillas et al 2014;Attaran 2017;Ben-Ner and Siemsen 2017;Durach et al, 2017;Feldmann and Pumpe 2017;Gao et al, 2015;Gress and Kalafsky 2015;Hasan et al, 2013;Holmström et al 2016;Holmström et al,2017;Holmström and Partanen 2014;Huang et al 2013;Joshi and Sheikh, 2015;Khorram Niaki and Nonino 2017;Kothman and Faber 2016;Oettmeier and Hofmann 2016;Ortt 2017;Rogers et al, 2016;Rogers et al,2017;Ryan et al 2017;Rylands et al 2016;Strong et al 2017;Sun and Zhao 2017;Wagner and Walton 2016;Woodson 2015) 25 SP + SC (Behfard et al 2015;Bergman et al 2017;Danas et al, 2006;de Souza et al 2011;Huiskonen 2001;Van Utterbeeck et al 2009;Wagner and Lindemann 2008) 7 AM + SP + SC (Holmström et al 2010;Khajavi, Partanen, and Holmström 2014;…”
Section: Appendix 1 Literature Included In the Reviewmentioning
confidence: 99%